MATHEMATICAL MODELING OF RANDOM DIFFUSION FLOWS IN TWO-PHASE MULTILAYERED STOCHASTICALLY NONHOMOGENEOUS BODIES - YEVHEN CHAPLYA; OLHA CHERNUKHA; ANASTASIIA DAVYDOK (TASK Quarterly, 2015)
An approach for studying stochastical diffusion flows of admixture particles in bodies of multiphase randomly nonhomogeneous structures is proposed, according to which initialboundary value problems of diffusion are formulated for flow functions and methods of solution construction are adapted for the formulated problems. By this approach the admixture diffusion flow is investigated in a two-phase multilayered strip for the uniform distribution of phases under conditions of constant flow on the upper surface and zero concentration of admixture on the lower surface. An integro-differential equation equivalent to the original initial-boundary value problem is constructed. Its solution is found in terms of the Neumann series. Calculation formulae are obtained for the diffusion flow averaged over the ensemble of phase configurations under both zero and constant nonzero initial concentrations. Software is developed, a dependence of averaged diffusion flows on the medium characteristics is studied and general regularities of this process are established.